Habitus dan Reproduksi Kultural Sunat Perempuan pada Masyarakat Muslim Sumenep: Habitus and Cultural Reproduction of Female Circumcision in Muslim Community of Sumenep - Ida Rosyidah; Joharotul Jamilah (Society, 2022)
Female circumcision has been widely studied in terms of the causal factors, the motivation of parents to choose female circumcision for medical or non-medical personnel, community knowledge about female circumcision, the relationship between female circumcision and human rights, and the impact of female circumcision on health. But this research focuses on how female circumcision is reproduced and transmitted to society. This study aims to examine how habitus influences agents in Sumenep Regency, Madura so that local agents carry out the reproduction and transmission of female circumcision. A qualitative approach method with the type of case study research is used to extract the data. The theory used in this research is habitus, field (arena), and reproduction of Bourdieu’s social practice. This study found that the social practice of female circumcision is a habit that has been going on for hundreds of years. So it has been internalized in society. Reproduction and transmission of the practice of female circumcision are carried out by various actors from different arenas/fields, both in education, health, and religious institutions. In addition, non-medical personnel such as traditional healers and nyai (calls for women older than the person calling) are also local agents who perform female circumcision reproduction.